Pulmonary Tumor Thrombotic Microangiopathy Secondary to Extramammary Paget’s Disease: An Autopsy Case Report and Literature Review - Kato, Akihiro; Kato, Hiroshi; Komori, Satoshi; Nakano, Satsuki; Murase, Takayuki; Nakamura, Motoki; Morita, Akimichi (Case Reports in Oncology, 2021)
Abstract Pulmonary tumor thrombotic microangiopathy is a fatal disease secondary to some malignant tumors, such as gastric cancer, esophageal cancer, and pancreatic cancer. A 61-year-old man presented to our clinic with a red plaque with erosion on his scrotum and was diagnosed with extramammary Paget’s disease. Seven years after the initial diagnosis, multiple bone metastases were discovered, and he was started on oral administration of tegafur/gimeracil/oteracil. Two years after beginning the oral drug administration, the patient complained of dyspnea. A chest CT scan showed ground-glass opacity. Pulmonary artery blood cytology revealed carcinoma cells. He was diagnosed with pulmonary tumor thrombotic microangiopathy. At 9 days after the diagnosis, he died of circulatory and respiratory failure. The autopsy revealed microscopic metastatic tumor emboli in multiple pulmonary vessels with fibrin thrombus, which confirmed the earlier cytologic diagnosis. Observations in our case were consistent with the typical pattern of this pathology in the lung with multiple metastases. Pulmonary tumor thrombotic microangiopathy with a primary disease of cutaneous malignancy is extremely rare. Here, we report a rare case of pulmonary tumor thrombotic microangiopathy secondary to extramammary Paget’s disease with a literature review.